KEMAMPUAN REPRODUKSI TUNGAU PREDATOR FAMILI PHYTOSEIIDAE PADA BERBAGAI KEPADATAN TETRANYCHUS URTICAE DAN POLEN TANAMAN DI SEKITAR TANAMAN SINGKONG (MANIHOT ESCULENTA CRANTZ) - Bambang Heru Budianto; Achmad Munadjat (Universitas Lampung, 2012)
The predatory mite of Phytoseiidae family have extensive cruising range that is not only found in cassava, but also a variety of weeds in cassava plants, such as Ageratum conyzoides and Cyperus cyperus. Extensive cruising range is also well explain the survival rate of the Phytoseiidae family at the time of the density of T. urticae decreased. The research objective is to determine the development period, fecundity and survival rate of Phytoseiidae predatory mite populations at different relative densities T. urticae and pollen. The research method used is an experimental laboratory. The procedure include the provision of A. conyzoides and C. rotundus pollen, the multiplication of predatory mite families Phytoseiidae, the determination of the development period, fecundity and survival rate of predatory mite families Phytoseiidae. The results showed that the length of time the development of predatory mites Amblyseius sp. and Phytoseius sp. faster one day of feeding on egg T. urticae feeding compared to the two types of pollen. Predatory mites survival rate Phytoseius sp. higher than the predatory mites Amblyseius sp. eggs fed T. urticae and both types of pollen. Similarly, the fecundity Phytoseius sp. higher than the mites Amblyseius sp. either fed eggs T. urticae as well as to two types of pollen.